A conservative foreign policy for Brazil. (24th October 2022) - Herz, Monica
Abstract: In this article, we put forward an interpretation of Jair Bolsonaro's foreign policy based on its attachment to a conservative authoritarian worldview. We look at how a conservative authoritarian movement and leadership interact with foreign policy in three different ways—by redefining the place of foreign policy in the wider social and political project of the government; by redesigning how the government prioritizes international relations with different countries; and, most importantly, by alienating the country's foreign policy from its longstanding support for multilateral institutions. Resumen: En este artículo presentamos una interpretación de la política exterior de Jair Bolsonaro anclada en una visión del mundo conservadora y autoritaria. Observamos cómo un movimiento conservador y de liderazgo autoritario interactúan con la política exterior de tres maneras diferentes: redefiniendo el lugar de la política exterior en el proyecto social y político más amplio del gobierno; rediseñando cómo el gobierno prioriza las relaciones internacionales con diferentes países; y, lo que es más importante, alejando la política exterior del país de su apoyo de larga data a las instituciones multilaterales. 摘要: 雅伊尔·博索纳罗在巴西执政后，与美国的政治结盟成为巴西外交政策的一个重要方面。尽管自特梅尔政府的权力真空期以来，巴西已经与华盛顿方面建立了密切联系，但博索纳罗和唐纳德·特朗普之间的极右翼意识形态协同作用变得更加明显。一个共同的、与反全球主义相互关联的反共立场反映了区域政治的共性以及国防和安全关系的显著加强。不过，博索纳罗和特朗普共同的世界观并没有在巴西的国际经济中蔓延开来。尽管与美国的政治关系占据重要地位，但巴西与中国的投资和贸易关系却得以维持甚至扩大。本文聚焦于博索纳罗‐特朗普时期的巴美关系。为了理解此关系，绘制了两条解释路径——使用比较历史概述追溯双边意识形态协同作用的过往，以评价博索纳罗‐特朗普双边主义的特征；对世界权力再分配过程加以情境化，该过程与中国的崛起相交织，深刻影响了美国的领导能力。 本文中，我们对雅伊尔·博索纳罗的外交政策进行解读，后者基于保守派的威权主义世界观。我们分析了保守的威权主义运动和领导层如何以三种不同的方式与外交政策相互影响，这三种方式分别为:1. 重新定义外交政策在更广的政府社会计划与政治计划中的地位；2. 对政府如何优先考虑与不同国家的国际关系一事进行重新设计；3. 使该国的外交政策远离其对多边制度的长期支持（这一方式最为重要）。